Usability of a Smartphone Application to Support the Prevention and Early Intervention of Anxiety in Youth. Issue 4 (November 2017) - Stoll, Ryan D.; Pina, Armando A.; Gary, Kevin; Amresh, Ashish
Abstract: Mental, emotional, and behavioral disorders are common in youth with anxiety problems being among the most prevalent, typically failing to spontaneously remit, and placing some youth at risk for additional difficulties. Mobile health (mHealth) might be a novel avenue to strengthen prevention efforts for child anxiety, since program effects are generally small. However, although a significant number of mHealth tools have been developed, few have been evaluated in terms of usability (or even clinical effectiveness). Usability testing is the first level of evaluation in responsible mHealth efforts as it is one of the main barriers to usage and adoption. As such, the objective of this research was to evaluate the usability of a smartphone application (app) corresponding to an indicated prevention and early intervention targeting youth anxiety. To accomplish this, 132 children ( M age  = 9.65, 63% girls) and 45 service providers ( M age  = 29.13, 87% female) rated our app along five established dimensions of usability (ease of use, ease of learning, quality of support information, satisfaction, and stigma). Findings showed that the app was highly and positively rated by youth and providers, with some variations (lower ratings when errors occurred). Path analyses also showed that system understanding was significantly related to greater system satisfaction, but that such relation occurred through the quality of support information offered by the app. Together, this has research and clinical implications as it highlights avenues for advancing youth care via mHealth usability evaluation, including prior to establishing effectiveness. Highlights: Presents an mHealth application to support child anxiety intervention. Evaluates usability as it is critical to reducing barriers to engaging in mHealth. High usability ratings and low stigma characterized our mHealth application. mHealth quality of support information emerged as a core usability dimension. Steps for evaluating usability in mHealth development and selection are outlined.